EVALUATION OF THE IMPACT OF THE SHARIA MINI BANK LABORATORY ON STUDENT COMPETENCE - Yoesoef, Yoesrizal Muhammad; Hayati, Husna; Khairisma, Khairisma; Syarif, Muhammad Fazlurrahman (FINANSIA : Jurnal Akuntansi dan Perbankan Syariah, 2024)
This study aimed to provide an overview concerning the role of the Islamic mini bank laboratory in improving student competence. A qualitative methodology was used comprising field observations, interviews, and document analysis. The results showed that there is a need for improved facilities, additional management members, and public-oriented promotions. Four empowerment models for Islamic mini bank laboratory were identified, with the fourth stage being the most effective in the context of "Mereka Belajar". The impact on the competence of student in Islamic banking has not reached the maximum potential due to the lack of compliance with the latest Islamic mini bank application standards. Therefore, it is very appropriate to have a better laboratory that follows the growth of Islamic banking. Aside from understanding the practice of Islamic mini bank laboratory, student must also be equipped with other competencies needed to compete and work effectively in Islamic banking.